2022
DOI: 10.37190/ppmp/145796
|View full text |Cite
|
Sign up to set email alerts
|

Effect and mechanism of depressant CK102 on flotation separation of fluorite and dolomite

Abstract: For a low grade dolomite type fluorite ore in the Hebei province, it was observed that the depressant CK102, a mixture of sulfuric acid, sodium silicate and aluminum sulfate, can effectively inhibit the gangue mineral dolomite in the flotation of fluorite. However, the inhibition mechanism of the depressant is still unclear. In this paper, the flotation separation performance and underlying mechanism of CK102 inhibiting dolomite were investigated through mineral flotation tests, adsorption measurements, infrar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
0
0
Order By: Relevance
“…In addition, infrared spectroscopy indicated that starch is mainly adsorbed through the hydroxyl group in starch molecule and Fe on hematite surface. Bai et al (2019) researched the effect of soluble starch on the separation effect of hematite and apatite, also confirmed that soluble starch is adsorbed on hematite surface via chemical adsorption of hydroxyl groups, but only weakly physical adsorption with apatite.…”
Section: Introductionmentioning
confidence: 79%
“…In addition, infrared spectroscopy indicated that starch is mainly adsorbed through the hydroxyl group in starch molecule and Fe on hematite surface. Bai et al (2019) researched the effect of soluble starch on the separation effect of hematite and apatite, also confirmed that soluble starch is adsorbed on hematite surface via chemical adsorption of hydroxyl groups, but only weakly physical adsorption with apatite.…”
Section: Introductionmentioning
confidence: 79%